Social media influencer and brand loyalty on generation Z: the mediating effect of purchase intention - Puput Alvhyona Pinto; Eristia Lidia Paramita (Diponegoro International Journal of Business, 2021)
Influencer marketing has become a new method of promoting a product or brand. The marketers believe that implementing influencer marketing appropriately may form a positive customer view of a product or brand so it can bring customers loyalty on the brand. This study aims to investigate the effect of influencers on brand loyalty of Generation Z with purchase intention as a mediating variable. Generation Z is a generation that is very close to technology even most of their life is spent to playing with social media. By expecting a marketing strategy that is close and easily accessible to generation Z, can create purchase intentions and loyalty at lower cost. The population is the Instagram users in Indonesia. Purposive sampling was used in this study by taking 200 samples. This research was conducted using path analysis and Sobel test to see the indirect effect. Before the path analysis is carried out, the reliability, validity and classical assumption tests are carried out first to see if the data obtained is appropriate for further analysis.  The result show that social media influencers can influence generation Z brand loyalty and purchase intentions are able to mediate social media influencers and generation Z brand loyalty.